Biochemical and histological effects of sitagliptin on Zucker Diabetic Fatty rat pancreas - Mega, C. (2013)
Background: Inhibition of dipeptidyl peptidase-4 (DPP-4) activity by sitagliptin has been shown to improve glycemic control in patients with type 2 diabetes Mellitus (T2DM) by prolonging the actions of incretin hormones, but the really impact of low-dose sitagliptin treatment on pancreas lesions is almost unknown. This study aimed to evaluate the effects of sitagliptin on biochemical and histological (pancreas) parameters of Zucker Diabetic Fatty (ZDF, fa/fa) rats, an animal model of T2DM. Methods: Diabetic (fa/fa) ZDF male rats were treated with vehicle or sitagliptin (10 mg/kg BW/day) during 6 weeks (n=8 each). The following parameters were assessed: serum glycaemia, HbA1c, insulin and lipid profile; serum and pancreas oxidative stress (MDA) and endocrine and exocrine pancreas histology, estimating and rating inflammatory infiltrate, fibrosis, vacuolization and congestion in a semiquantitative score ranging from 0 (minimal) to 3 (severe and extensive damage). Results: Sitagliptin in diabetic ZDF rats promoted beneficial effects on dysglycaemia, dyslipidaemia, inflammatory profile and pancreatic oxidative stress. Endocrine and exocrine pancreas presented a reduction/amelioration of fibrosis severity, inflammatory infiltrate, intra-islet vacuolation, and congestion vs the vehicle-treated diabetic rats. Conclusions: The favourable biochemical profile promoted by sitagliptin in the diabetic rats, together with a protection against endocrine and exocrine pancreas lesions, might represent a further advantage of low doses of sitagliptin in the management of T2DM.